Health economic implications of complications associated with pancreaticoduodenectomy at a University Hospital: a retrospective cohort cost study. Issue 5 (May 2018) - Wang, Jason; Ma, Ronald; Eleftheriou, Paul; Churilov, Leonid; Debono, David; Robbins, Ray; Nikfarjam, Mehrdad; Christophi, Chris; Weinberg, Laurence
Abstract: Background: A cost analyses of complications following pancreaticoduodenectomy (PD) was performed in a high volume hepato-biliary-pancreatic service. We hypothesised that costs are increased with both severity and number of complications; we investigated the relationship between complications and specific cost centres. Methods: 100 patients from 2011 to 2016 were included. Data relating to their perioperative course were collected. Complications were documented by the Clavien–Dindo classification and costs were inflated and converted to 2017 USD. Results: Mean hospital costs in complicated patients more than doubled those of uncomplicated patients ($28 330 vs. $57 150, p < 0.0001). Total hospital costs significantly increased with both severity and number of complications. This cost increase was influenced by medical consult, pathology, pharmacy, radiology, ward, intensive care, and allied health costs, but not operating theatre or anaesthesia costs. Postoperative pancreatic fistula, postoperative haemorrhage, delayed gastric emptying and infection were associated with cost differentials of $65 438, $74 079, $35 620 and $46 316 respectively over uncomplicated patients. Conclusion: The development of complications following PD is common, costly and associated with increased length of stay. Costs increased with greater complication severity, and specific complications. The in-depth breakdown of hospital costs suggests specific targets for cost containment.